ChemInform Abstract: Structural and Magnetocaloric Properties of Novel Gadolinium Borohydrides. Issue 18 (April 2016) - Schouwink, Pascal; Didelot, Emilie; Lee, Young‐Su; Mazet, Thomas; Cerny, Radovan
Abstract: An Gd(BH4 )n+3 (A: K, Cs) are prepared by ball milling of appropriate amounts of alkali borohydrides and Gd(BH4 )3 under an inert atmosphere (600 rpm, 2 min, 60 repetitions; 5 min cooling break).